Unveiling the Tapestry: Exploring TikTok Usage among Generation Z in Pakistan - Dr Maimoona Saleem; Dr. Sonia Sethi; Dr Rabia Naseer; Dr Adeeba Khan; Dr Syed Noman Mustafa (Al-Qanṭara, 2023)
This study digs into the complex web of TikTok use among Pakistan’s Generation Z, looking at the underlying trends, driving forces, and outcomes. The research uses a qualitative methodology and asks 84 participants, all members of the Gen Z cohort, to respond to real-life scenarios presented as vignettes. Each participant read the vignette provided and then responded to a series of open-ended questions. Vignettes were used as a special lens to examine the complex world of TikTok participation. The research attempted to record genuine responses that resembled real-life behavior by placing participants in relevant circumstances. This approach helped illuminate the underlying dynamics that underlie participant engagement by facilitating a comprehensive understanding of their motives and interactions with the platform. Reflexive thematic analysis was performed on the obtained data to reveal the rich tapestry of participant insights. Five themes thus emerged, each of which provided insight into the intricate interactions between Generation Z, TikTok, and Pakistani socio-cultural dynamics. 1) Gratifications Sought by Pakistani Gen Z TikTok Users 2) TikTok is Warping our Perception of Ourselves 3) The Influence of TikTok Content on Morality and Ethics 4) TikTokers’ Authenticity and Trustworthiness 5) The Ineffectiveness of Imposing Restrictions and Banning TikTok. The study’s findings shed light on the factors that motivate Gen Z users of TikTok, from self-expression and amusement to social connection and cultural representation. The effects of TikTok’s involvement are also investigated, revealing benefits like encouraging innovation and cultural preservation and drawbacks like privacy problems and the possibility of spreading false information. This research adds to the body of knowledge on social media engagement and young culture by exploring the nuances of TikTok use among Pakistan’s Generation Z. Utilizing vignettes as a research tool gives a novel methodological angle that enables genuine and contextually based findings. These results provide insightful information for academics, decision-makers, and platforms looking to comprehend better and serve Pakistan’s dynamic Generation Z cohort as the digital environment changes.